Lean principles for Scrum LiveLessons - Norman, Tommy (Addison-Wesley Professional, 2016)
"For companies that have implemented Scrum, applying Lean will amplify their Scrum implementations and development cycles. This video course will demonstrate how to apply Lean methods to Scrum."--Resource description page.